Honoring the code : conversations with great game designers - Barton, Matt (A K Peters/CRC Press, 2016)
"If you want to be successful in any area of game development--game design programming graphics sound or publishing--you should know how standouts in the industry approach their work and address problems. In Honoring the Code: Conversations with Great Game Designers 16 groundbreaking game developers share their stories and offer advice for anyone aspiring to a career in the games industry. You'll learn from their triumphs and failures and see how they dealt with sweeping changes in technology including critical paradigm shifts from CD-ROMs and 3D graphic cards to the Internet and mobile revolution. The book presents in-depth interviews with a diverse mix of game professionals emphasizing the makers of adventure games role-playing games and real-time strategies. It focuses on developers who have contributed to multiple eras or genres as well as those who have hired taught or mentored newcomers. Since the mobile revolution has opened up new demographics and new gameplay mechanics the book features current developers of games for mobile devices. It also explores how indie game developers are making commercial-quality games with a small team mostly using free tools and funded with crowdsourcing applications. While there are plenty of resources available for aspiring game developers to learn the necessary technical skills there is hardly any historical material on the culture that made the games industry possible. Filling the void this book provides a historical and cultural context for the games industry. It takes you into the minds of the pioneers who blazed the trails and established the industry as we know it today."